Mengidentifikasi Faktor-faktor yang Mempengaruhi Wakaf Uang di Kota Palembang - Hamidi, Ichsan; Hamira, Hamira; Sari, Dwi Darma Puspita; Bashir, Abdul (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2023)
The purpose of this study is to determine the factors that influence cash waqf in Palembang City. This research was conducted in Palembang City with an unknown population, so we used Lemeshow formula to decide the respondents who did a cash waqf and were obtained by distributing questionnaires. Multiple linear regression is used in this study. Based on the results of data analysis, it shows that simultaneously all independent variables such as income, education, technology or media information, and religiosity have a positive and significant effect on cash waqf. Partially income, technology or media information, and religiosity have a positive and significant effect on cash waqf, while education has a positive but not significant effect. The results of this study are expected to encourage the potential of cash waqf to increase economic growth. Although cash waqf is not an obligation, special regulations in the form of cash waqf recommendations, especially for workers, are expected to encourage someone’s interest in doing cash waqf.